2013
DOI: 10.1111/cas.12204
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of neuroblastoma cell lines in insulin‐like growth factor 1 receptor/Akt pathway‐mediated cell proliferative responses

Abstract: Insulin-like growth factor 1 receptor (IGF-1R) is critical for cancer cell proliferation; however, recent clinical anti-IGF-1R trials did not show clear clinical benefit in cancer therapy. We hypothesized that IGF-1R signaling-mediated proliferative response is heterogeneous in neuroblastoma (NB) cells, and analyzed the cell growth of 31 NB cell lines cultured in three different media, including Hybridoma-SFM medium (with insulin) and RPMI1640 with ⁄ without 10% FBS. Three growth patterns were found. In respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…Indeed, IGF1R signaling, which plays an important role in cancer cell proliferation, has been shown to play a role in the neuroblastoma malignant phenotype (41)(42)(43)(44). Furthermore, in 2 cases, an alteration targeting TERT, shown recently to characterize aggressive high-risk neuroblastoma (45,46), was identified in the cfDNA, with one case harboring this alteration also in the metastatic tumor cells of the bone marrow but not in the primary neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, IGF1R signaling, which plays an important role in cancer cell proliferation, has been shown to play a role in the neuroblastoma malignant phenotype (41)(42)(43)(44). Furthermore, in 2 cases, an alteration targeting TERT, shown recently to characterize aggressive high-risk neuroblastoma (45,46), was identified in the cfDNA, with one case harboring this alteration also in the metastatic tumor cells of the bone marrow but not in the primary neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the sensitivity to m708.5 correlated with the high expression of IGF‐1R and/or IR‐A; however, this sensitivity to m708.5 was not uniform. Recent studies suggested that neuroblastoma cells were heterogeneous in their IGF‐1R pathway‐mediated cell proliferation . Constitutive activity of downstream signals ( e.g ., PI3K/Akt) independent of the IGF‐1R or IRA pathways could explain part of the heterogeneity of response between neuroblastoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that neuroblastoma cells were heterogeneous in their IGF-1R pathway-mediated cell proliferation. 36 Constitutive activity of downstream signals (e.g., PI3K/Akt) independent of the IGF-1R or IRA pathways could explain part of the heterogeneity of response between neuroblastoma cell lines. In vivo, m708.5 alone (4 mg/kg/dose, twice weekly for 3-4 weeks) significantly delayed neuroblastoma growth.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous molecular studies have demonstrated that the Akt signal transduction cascade usually participates in ES cell progression, cell apoptosis, cell proliferation and drug susceptibility (32)(33)(34). As an IFG-1R inhibitor, PPP was found to have Akt inhibitory effects in neuroblastoma cell lines (35). Furthermore, the efficacy of PPP against multiple myeloma has also been demonstrated (31).…”
Section: Discussionmentioning
confidence: 99%